Protective Role of Spirulina on the Variation of Haematological Parameter Induced by Herbicide Atrazine in the Fresh water Fish Cyprinus carpio (Linn) - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The protective effect of Spirulina against atrazine toxicity stress and haematological parameters was evaluated in fresh water fish Cyprinus carpio (Linn). Exposure to atrazine along with Spirulina for 120 hours by an acute toxic dose 0.5 mg/L showed variation in the haematological parameters. Spirulina treatment shows marked elevation in the blood haemoglobin, RBC and haematocrit and the recovery was noticed. Atrazine induced haematological change were also minimized with the treated atrazine along with Spirulina. The observed level of WBC is increased (group II), when compared with control. These results suggest the Spirulina algae might play a role in reducing the toxic effect of atrazine and Sits haematological effects seem to mediate such a protective effect.